2021
DOI: 10.3390/molecules26134013
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Energy-from-Waste Approach for Electrical Energy Production by Galvano–Fenton Process

Abstract: A novel approach allowing the production of electrical energy by an advanced oxidation process is proposed to eliminate organic micropollutants (MPs) in wastewaters. This approach is based on associating the Galvano–Fenton process to the generation of electrical power. In the previous studies describing the Galvano–Fenton (GF) process, iron was directly coupled to a metal of more positive potential to ensure degradation of organic pollutants without any possibility of producing electrical energy. In this new a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…At present, we suggest relating the efficiency of the Galvano-Fenton to the energy release (Gasmi et al 2021), compared to the efficiency of the electro-Fenton process to the energy consumption, considering similar conditions of spontaneous and forced electrochemical reactions. The polarization curves of the Fe-Cu galvanic cell within the Galvano-Fenton process with the configuration described earlier showed that the corrosion current is estimated at 298.75 µA for a corrosion potential of 0.277 V, which is equivalent to a maximum power of 82.75 mW.…”
Section: Energetic Performance Of the Techniquementioning
confidence: 99%
“…At present, we suggest relating the efficiency of the Galvano-Fenton to the energy release (Gasmi et al 2021), compared to the efficiency of the electro-Fenton process to the energy consumption, considering similar conditions of spontaneous and forced electrochemical reactions. The polarization curves of the Fe-Cu galvanic cell within the Galvano-Fenton process with the configuration described earlier showed that the corrosion current is estimated at 298.75 µA for a corrosion potential of 0.277 V, which is equivalent to a maximum power of 82.75 mW.…”
Section: Energetic Performance Of the Techniquementioning
confidence: 99%
“…At present, we suggest relating the efficiency of the Galvano-Fenton and Galvano-Fenton process with pre-immersion time to the energy release [31], compared to the efficiency of the electro-Fenton process to the energy consumption, considering similar conditions of spontaneous and forced electrochemical reactions. Figure 9a represents the polarization curves of the Fe-Cu galvanic cell within the Galvano-Fenton process in the presence of hydrogen peroxide at 0.187 mM, as described in the present work.…”
Section: Energetic Insightsmentioning
confidence: 99%
“…Thus, the Galvano-Fenton process does not require any external current and, on the contrary, produces energy along with the oxidation of target pollutants. From a technological point of view, the energetic outcomes of the Galvano-Fenton process have been recently studied as a novel approach for energy from waste [25], and estimations have been made in terms of energy production and saving, using the basic configuration as well as an upgraded one relying on a pre-immersion stage of the electrodes in the electrolyte [24]. Economically speaking, a direct comparison with the classic Fenton process clearly shows that the Galvano-Fenton eliminates the need for ferrous salt addition, which prevents at least an additional operation cost related to the use of ferrous sulfate heptahydrate salt as a catalyst source [26].…”
Section: Introductionmentioning
confidence: 99%